A prominent figure for the “living human treasures list” in meddah-ship: Yusuf sıra from kadirli - Şimşek, Esma (Milli Folklor Dergisi, 2015)
Story telling tradition which is not alive as it was before, is still keeping alive in Cukurova region. Those who lived in this tradition is Yusuf Sıra who lives in Bekereci village of Kadirli. He known as “Ashik Yusuf and a master storyteller who continues the tradition of “meddah-ship” by various aspects. Yusuf Sıra who narrates beautiful tales with his ability to imitation, imagination and wit, tells the Güzel Ahmet and Esma Han tales in addition to Köroğlu tales that he learned from the ashiks who came their house at his childhood and he tells them properly. Also he knows some of türküs (Bey Kızı and Hüseyin, Çöllo, Karacaoğlan and Hacı) that involves a short tale. Moreover, Sıra performs “Göde”, “Deve”, “Kocakarı”, “Sinsin” and “Serçe” spectacles which are performed at the villages, serves “Abdal Ağa” duty during the weddings and leads Anatolian folk dance called “halay”. Yusuf Sıra has learned playing “kaval” while he was a shepherd, and he also plays “sipsi”. Sıra is a very good anecdote teller as well as being a poet. Yusuf Sıra who shows skills of a “meddah” in many aspects, is a performer who has introduced himself to the science world as having two graduate thesis, two papers, four articles on him. He, with the specialties above, is one of the names who must be added to the UNESCO’s “Living Human Treasures List” like Neşet Ertaş, Şeref Taşlıova, Maksut Koca, Halime Öğüt, Mehmet Gürsoy etc. In this article, Yusuf Sıra’s tale telling in other words meddah-ship will be evaluated from many aspects and justifcations will be given that why he has to be added to the “Living Human Treasures List”. © 2015, Milli Folklor Dergisi. All rights reserved.
Meddahlikta, “yaşayan insan hazineleri listesi”ne eklenmesi gereken bir isim: Kadirlili yusuf sira
Keywords: Kadirli; Living human treasure; Meddah; Storyteller; Yusuf sıra